2017
DOI: 10.3390/su9030380
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of GIS Overlay and PCA Techniques for Urban Environmental Quality Assessment: A Case Study in Toronto, Ontario, Canada

Abstract: Abstract:The United Nations estimates that the global population is going to be double in the coming 40 years, which may cause a negative impact on the environment and human life. Such an impact may instigate increased water demand, overuse of power, anthropogenic noise, etc. Thus, modelling the Urban Environmental Quality (UEQ) becomes indispensable for a better city planning and an efficient urban sprawl control. This study aims to investigate the ability of using remote sensing and Geographic Information Sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 53 publications
(73 reference statements)
1
30
0
Order By: Relevance
“…The dependent parameter indicates the UEQ outcome, which was derived from GIS overlay method. That is mainly because the GIS overlay was found to be more emblematic for UEQ in some previous studies and one of our parallel studies [5,15]. The independent parameters are the urban and environmental parameters, which were derived from the remote sensing and GIS data, such as population density, building density, NDVI, public transportation, etc.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…The dependent parameter indicates the UEQ outcome, which was derived from GIS overlay method. That is mainly because the GIS overlay was found to be more emblematic for UEQ in some previous studies and one of our parallel studies [5,15]. The independent parameters are the urban and environmental parameters, which were derived from the remote sensing and GIS data, such as population density, building density, NDVI, public transportation, etc.…”
Section: Methodsmentioning
confidence: 85%
“…These integration techniques are able to assess the current and predict/estimate the future UEQ, which are modelled by the municipal and city planners [4]. Thus, the assessment of UEQ can be an efficient tool to provide effective information of urban conditions, sustainable development and regional planning [5]. UEQ can be modelled using satellite remote sensing techniques through analysing multi-temporal and multi-resolution data, which are able to give a clear vision for visualizing and understanding the land cover, Land Surface Temperature (LST), water conditions and vegetation in urban areas [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration techniques, including GIS overlay and Principle Component Analysis, were used to integrate environmental, urban, and socio-economic parameters. The approach can provide fruitful information to model UEQ; however, due to the lack of significance the practical application of this indicator may be limited [24].…”
mentioning
confidence: 99%
“…Klimas et al [16] confirmed that incorporating knowledge of small-scale variability in ESs and in disservices on parcel-sized lots (private or public) may improve sustainable planning in urban areas. Faisal and Shaker [24] modeled the Urban Environmental Quality (UEQ) for better city planning and efficient urban sprawl control. Integration techniques, including GIS overlay and Principle Component Analysis, were used to integrate environmental, urban, and socio-economic parameters.…”
mentioning
confidence: 99%